Death of the ALARA Radiation Protection Principle as Used in the Medical Sector - Paul A. Oakley; Deed E. Harrison (SAGE Publishing, 2020)
ALARA is the acronym for "As Low As Reasonably Achievable." It is a radiation protection concept borne from the linear no-threshold (LNT) hypothesis. There are no valid data today supporting the use of LNT in the low-dose range, so dose as a surrogate for risk in radiological imaging is not appropriate, and therefore, the use of the ALARA concept is obsolete. Continued use of an outdated and erroneous principle unnecessarily constrains medical professionals attempting to deliver high-quality care to patients by leading to a reluctance by doctors to order images, a resistance from patients/parents to receive images, subquality images, repeated imaging, increased radiation exposures, the stifling of low-dose radiation research and treatment, and the propagation of radiophobia and continued endorsement of ALARA by regulatory bodies. All these factors result from the fear of radiogenic cancer, many years in the future, that will not occur. It has been established that the dose threshold for leukemia is higher than previously thought. A low-dose radiation exposure from medical imaging will likely upregulate the body's adaptive protection systems leading to the prevention of future cancers. The ALARA principle, as used as a radiation protection principle throughout medicine, is scientifically defunct and should be abandoned.